2015
DOI: 10.1007/978-3-319-16712-1_6
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetic Studies in the Adsorption of Hazardous Substances Using Clay Minerals

Abstract: For the design of the adsorption system, reliable adsorption kinetic data are required. Different concepts are employed to develop a reliable adsorption kinetic model. Most of the available models were developed according to mass transfer principles or the concept of chemical reaction occurring on the surface of a solid. The models based on the surface-reaction kinetic step as controlling the sorption rate have also been proposed, these models include pseudo-first order kinetic (also called as Lagergren model)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Adsorption kinetic models play a key role to determine the mechanisms involved in the sorption of solid-liquid systems [96]. In this work, the experimental data were tested against the Weber-Morris and the allometric models (Equations (1) and ( 2)).…”
Section: Kinetics Studies Of Hg Removalmentioning
confidence: 99%
“…Adsorption kinetic models play a key role to determine the mechanisms involved in the sorption of solid-liquid systems [96]. In this work, the experimental data were tested against the Weber-Morris and the allometric models (Equations (1) and ( 2)).…”
Section: Kinetics Studies Of Hg Removalmentioning
confidence: 99%
“…The three parameters of Sips isotherm are an extended Langmuir-Freundlich model (Ismadji et al 2015) and are shown in Eq. (12).where q mS is the maximum loading capacity (mg g −1 ), K S is the adsorption affinity, and n S is the system's heterogeneity.…”
Section: Effect Of As(v) Concentration and Adsorption Isothermmentioning
confidence: 99%